2013
DOI: 10.1111/trf.12088
|View full text |Cite
|
Sign up to set email alerts
|

Microparticle formation in apheresis platelets is not affected by three leukoreduction filters

Abstract: Although the conditions of this study showed no favorable or unfavorable effects of three different filters on microparticle formation, surveillance and investigation of unanticipated outcomes in other experimental and clinical circumstances should continue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 17 publications
2
10
1
Order By: Relevance
“…There remains debate as to whether LR leads to a decrease in MPs. Similar to the presented data, LR of apheresis Plt concentrates did not affect MP formation (Nollet et al , ). In contrast, the same research group demonstrated that whole blood LR did decrease MP formation (Sugawara et al , ).…”
Section: Discussionsupporting
confidence: 91%
“…There remains debate as to whether LR leads to a decrease in MPs. Similar to the presented data, LR of apheresis Plt concentrates did not affect MP formation (Nollet et al , ). In contrast, the same research group demonstrated that whole blood LR did decrease MP formation (Sugawara et al , ).…”
Section: Discussionsupporting
confidence: 91%
“…WBC filtration of whole blood was reported to lower PMP and LMP counts during storage . However, a previous study reported that WBC filtration of apheresis PLT products had virtually no effects on the formation of PMPs, RMPs, and LMPs . Our work further suggested that WBC filtration exerted no effects on the formation of MMPs and EMPs.…”
Section: Discussionsupporting
confidence: 67%
“…Multiple studies have reported that PMPs are generated during storage of apheresis PLTs ex vivo . MPs originating from red blood cells (RBCs), lymphocytes, monocytes, and endotheliocytes in circulating blood may enter PLT supernatants . As a measurable amount of their parental cells are contained in the apheresis PLT products, these MPs may be generated during the time of storage.…”
mentioning
confidence: 99%
“…Despite the high amount of PLT microparticles generated in response to cryopreservation, the numbers decreased during storage at room temperature for 24 hours. This result was counterintuitive, as microparticle numbers have been shown to increase during extended storage (14 days) of apheresis PLTs . An explanation for this result may be due to the way that the microparticles have been defined in this study, by dual expression of CD61 and phosphatidylserine.…”
Section: Discussionmentioning
confidence: 70%